509 Splenosis, an Important Differential for Peritoneal Metastases. (19th August 2022) - Tanwar, A; Gurung, C; Pangeni, A; Shrestha, A; Basnyat, P
Abstract: Splenosis is defined as the auto-transplantation of splenic tissues in other sites of the body. It is a rare benign condition and can be an incidental finding. However, early diagnosis is essential as the differential diagnosis of splenosis includes peritoneal metastases. Early identification relies on recognising relevant past medical history including splenic injury and or splenectomy. Splenosis can be confirmed through the usage of a technetium-99m colloid scan. By using nuclear medicine scans, repeated invasive investigations such as biopsy and diagnostic laparoscopies can be avoided. We present here a case of a 51-year-old woman who was extensively investigated by the gynaecology department and general surgery department, even undergoing a diagnostic laparoscopy following repeated presentations to primary and secondary care with chronic abdominal and pelvic pain. She had a splenectomy 28 years earlier for traumatic splenic injury. CT scan of abdomen and pelvis showed features suspicious of multiple peritoneal metastases and hence she was urgently referred to a colorectal cancer multidisciplinary meeting. A subsequent technetium-99m colloid scan confirmed multiple splenic nodules in the peritoneal cavity. The patient was reassured and discharged. In conclusion, in a patient with a known history of splenic trauma, splenosis is an important differential diagnosis. A careful past medical history and appropriate investigations will avoid unnecessary referral and invasive investigations.